Influence of sodium chlorate, ferulic acid, and essential oils on Escherichia coli and porcine fecal microbiota. (17th February 2020) - Arzola-Alvarez, Claudio; Hume, Michael E; Anderson, Robin C; Latham, Elizabeth A; Ruiz-Barrera, Oscar; Castillo-Castillo, Yamicela; Olivas-Palacios, Ana Luisa; Felix-Portillo, Monserrath; Armendariz-Rivas, Ruth L; Arzola-Rubio, Alejandro; Ontiveros-Magadan, Marina; Bautista-Martínez, Yuridia; et al.
Abstract: The influence of sodium chlorate (SC ), ferulic acid (FA ), and essential oils (EO ) was examined on the survivability of two porcine diarrhetic enterotoxigenic Escherichia coli (ETEC ) strains (F18 and K88) and populations of porcine fecal bacteria. Fecal bacterial populations were examined by denaturing gradient gel electrophoresis (DGGE ) and identification by 16S gene sequencing. The treatments were control (no additives), 10 mM SC, 2.5 mg FA /mL, a 1.5% vol/vol solution of an EO mixture as well as mixtures of EO + SC, EO + FA, and FA + SC at each of the aforementioned concentrations. EO were a commercial blend of oregano oil and cinnamon oil with water and citric acid. Freshly collected porcine feces in half-strength Mueller Hinton broth was inoculated with E. coli F18 (Trial 1) or E. coli K88 (Trial 2). The fecal- E. coli suspensions were transferred to crimp top tubes preloaded with the treatment compounds. Quantitative enumeration was at 0, 6, and 24 h. All treatments reduced ( P < 0.05) the counts of E. coli F18 at 6 and 24 h. With the exception of similarity coefficient (%SC ), all the other treatments reduced ( P < 0.05) the K88 counts at 24 h. The most effective treatments to reduce the F18 and K88 CFU numbers were those containing EO. Results of DGGE revealed that Dice percentage similarity coefficients (%SC) of bacterial profiles among treatment groups varied from 81.3% to 100%SC. The results of gene sequencing showed that, except for SC at 24 h, all the other treatments reduced the counts of the family Enterobacteriaceae, while Lactobacillaceae and Ruminococcaceae increased and Clostridiaceae decreased in all treatments. In conclusion, all treatments were effective in reducing the ETEC, but EO mixture was the most effective. The porcine microbial communities may be influenced by the studied treatments.